Research on the effect of sizing agent on the interface and compression performance of carbon fiber composites - Ouyang, Xinfeng; Ge, Guojie; Geng, Yizhi; Zong, Yangyang; Pan, Tong; Wang, Xiao; Zhu, Weiwei; Bai, Yuefeng; Liu, Yunpeng; Duan, Shuo; Niu, Kangmin (Frontiers in Materials, 2024)
The present study involves the preparation of continuous carbon fiber samples treated with epoxy-based sizing agent (EP) and vinyl ester resin-based sizing agent (VE), alongside untreated fibers, aiming to explore the influence pattern of interfacial differences caused by these sizing agents on the compressive properties of carbon fiber composites. Surface analysis, including Scanning Electron Microscope (SEM), Atomic Force Microscope (AFM), and X-ray Photoelectron Spectroscopy (XPS), followed by testing the mechanical properties of carbon fibers and the composite materials. Results indicate that, compared to unsized carbon fibers, EP and VE increase the O atom content on the carbon fiber surface by 13.0% and 18.1%, respectively, and enhance the proportion of active C atoms by 11.3% and 20.3%, respectively. The interlaminar shear strength (GB/T) of carbon fibers is improved by 9.3% and 20.0%, respectively. Given the compatibility between the sizing agent and the matrix resin, VE improves the open-hole compressive strength of composites by 6.7% compared to EP. This improvement in interface bonding performance positively impacts the open-hole compressive properties of the composites, though it has limited effect on the 0° compressive and post-impact compressive strengths. Following EP and VE sizing, the 0° compressive strength increases by 11.8% and 13.6%, respectively, with VE only resulting in a marginal 1.6% improvement over EP. The enhancements in both interlaminar shear strength and open-hole compressive strength are attributed to the increased number of active functional groups at the fiber-resin interface, facilitated by sizing agents, which promote stronger chemical bonding and thus improved load transfer between the fibers and the matrix. VE demonstrates superior performance over EP in regulating the interface state of carbon fibers.The presence or absence of a sizing agent has a more significant impact on the compressive properties of carbon fiber composites than the type of sizing agent used. These findings provide valuable insights for optimizing the preparation and enhancing the compressive performance of carbon fiber composite materials.